Perbandingan Model Persamaan Akuntansi dalam Menghasilkan Kompetensi Mahasiswa: Penelitian Eksperimen - Yanto Darmawan (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2013)
Based on Scaffolding Theory, accounting equation can be used as an aid for novice learners when studying journalizing transactions (Philip and Heiser, 2011). Accounting text books indicates the accounting equation by a notation Assets = Liabilities + Equity + Revenues - Expenses. But there is also a notation declared in the form of Assets + Expenses = Liabilities+ Equity + Revenues. This study aimed to investigate whether the use of two models accounting equation will make a difference in determining the normal account balances and transactions journalizing skills. To that end, formed two groups given different treatments. Participants are students first semester consisting of 64 students in treatment group A and 58students in the treatment group B. Skills in the determination of the normal account balances and transactions journalizing is measured by the ability of participants completed the 27 multiple choice questions. Statistical testing using the Independent Samples T-Test shows that statistically there is a difference between the two models accounting equation ingenerating skills in determining normal balance and journalizing transaction for transactions that affect only balance sheet accounts. However, there is no difference to the transactions that affect both balance sheet and income statement accounts.